Penerapan Model Problem Based Learning Dalam Meningkatkan Hasil Belajar PAI di Kelas XI SMKN 1 Lintau Buo - Nurafifah Afna (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education through the Problem-Based Learning (PBL) model in class XI Mechanical Engineering at SMKN 1 Lintau Buo. This Classroom Action Research (CAR) was conducted in two cycles, including planning, implementation, observation, and reflection stages. In the pre-cycle stage, students' learning outcomes were low, with a mastery level of only 43%. After implementing the PBL model, significant improvement was observed in cycle II, with learning mastery reaching 87.5%. This success was attributed to the problem-based approach, which motivated students to actively engage in the learning process, think critically, and solve relevant problems. Thus, the implementation of PBL has proven effective in enhancing students' learning outcomes in Islamic Religious Education.